Aplikasi bokashi jerami padi dan kotoran kelelawar terhadap pertumbuhan tanaman Paria (Momordica charantia L.) varietas Raden - Sartia Hama (Fakultas Pertanian Universitas Majalengka, 2026)
This study aimed to evaluate the effect of rice straw bokashi and bat guano application on the growth of bitter melon (Momordica charantia L.) cv. Raden and to determine the most effective treatment combination. The experiment was conducted in Witaponda District, Morowali Regency, Indonesia, from August to October 2024 using a Randomised Complete Block Design (RCBD) consisting of five treatments and five replications. The treatments included P0 (control), P1 (50 g rice straw bokashi + 200 g bat guano), P2 (100 g rice straw bokashi + 150 g bat guano), P3 (150 g rice straw bokashi + 100 g bat guano), and P4 (200 g rice straw bokashi + 50 g bat guano). The observed parameters were plant height, number of leaves, number of branches, and flowering age. Data were analysed using analysis of variance (ANOVA), followed by correlation analysis to determine the relationship between plant height and leaf number. The results showed that the application of rice straw bokashi and bat guano positively affected the growth of bitter melon. The P4 treatment produced the best growth performance, with a plant height of 140 cm, 35 leaves per plant, the highest number of branches, and the earliest flowering age of 23.75 days after planting (DAP). The combination of bokashi and guano improved nutrient availability, enhanced soil physical and biological properties, and stimulated microbial activity, thereby promoting both vegetative and generative growth. Correlation analysis revealed a strong positive relationship between plant height and leaf number (r = 0.84), indicating balanced plant development. These findings demonstrate that the application of 200 g rice straw bokashi combined with 50 g bat guano is the most effective treatment for improving growth and accelerating flowering of bitter melon cv. Raden has potential as an environmentally friendly organic fertilisation strategy.